Diversifying water storage choices supports river basin decision-makers - CGIAR Initiative on NEXUS Gains (CGIAR System Organization, 2024)
Implementing diverse water storage solutions is a cost-effective way of enhancing water security in semi-arid catchments. An integrated storage approach advocated by NEXUS Gains is finding favor with water resource managers in transboundary basins, where local storage decisions can have far-reaching basin-wide impacts. Using NEXUS Gains research, managers are able to opt for ‘green’ water storage options as sustainable alternatives to large ‘gray’ infrastructure. The successful application of this approach in two catchments – located in different regions of Africa – demonstrates its potential for larger-scale implementation.